LITERATURE REVIEW:POLA MAKAN SEHAT DALAM MASYARAKAT TERHADAP KESEHATAN DAN GIZI - Adekha Herdiani br Butar Butar (Jurnal Kesehatan, 2024)
Diet is an effort to control the amount and type of food while still providing an overall picture, such as nutritional status, maintaining health, and avoiding or treating disease (MOH RI, 2016). Food consumption patterns can be adjusted to suit needs by choosing good types and ingredients of food to achieve optimal nutritional value. Consuming too much food to meet human needs can lead to obesity, which poses risks associated with excess nutrition. This research aims to provide insight to the public in managing their diet. The method used is a literature study by taking data from various existing literature and journals, then analyzing the problem of correct dietary pattern management. Several pieces of literature are used and in the end it can be concluded that people's diet has a significant impact on health and nutrition. Factors such as the habit of consuming foods high in fat and added sugar can increase the risk of non-communicable diseases, nutritional deficiencies, obesity and other health problems.